Promoting the health and well-being of English-speaking seniors in Quebec. A community model - Kueber, Rusell (Community Health and Social Services Network, 2019)

Promotion de la santé et du bien-être des aînés d’expression anglaise du Québec : un modèle communautaire - Kueber, Russell (Réseau communautaire de santé et de services sociaux, 2019)

Modèle de mobilisation communautaire pour l’amélioration de la santé et de la vitalité des communautés d’expression anglaise au Québec - Kueber, Russell; Richardson, Mary (Réseau communautaire de santé et des services sociaux et Institut national de santé publique du Québec, 2019)

Social service accessibility in Montreal’s English-speaking disability community: A needs-based assessment - Nash, Aubrey (McGill University, 2019)
Health and social service systems can be difficult to traverse, especially in the stressful situations that often necessitate accessing them. In Quebec, these difficulties are exacerbated for English speaking or limited French-proficient persons. This thesis employs a needs-based assessment to explore how linguistic-based access barriers to health and social services affect Montreal’s English-speaking Disability community, focusing on those with intellectual and/or developmental disabilities and their caregivers/advocates. It identifies the community’s needs and proposes three key issues that result in the needs being unmet by the social service system. Specifically, the issues are (i) inaccessible information for limited French-proficient persons, as many important documents are available in only French; (ii) the primary method for bolstering language congruency between service users and providers relies on the service seeker to acquire French, which is incompatible with the lived experiences of many members of the Disability community; (iii) limited options for English services across Montreal. This thesis indicates the protection of the French language under the Charter of the French Language (1977) impacts the ability of the Act Respecting Health Services and Social Services (1991) to protect the rights of English-speaking Quebeckers to receive services in English. Through a human rights model of Disability and citizenship lens, it suggests that language laws can be understood and implemented to protect the Quebecois identity while ensuring active inclusion of otherwise marginalized communities in health and social service systems

Pratique # 15 : Le volet « santé et services sociaux » de l’Association des Townshippers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2019)
Le volet « santé et services sociaux / Health and Social Services » de l’Association des Townshippers a pour but de créer des ponts entre, d’une part, la population d’expression anglaise résidant dans les Cantonsde-l’Est et, d’autre part, les organisations de services sociaux et de santé et les professionnel·les qui y œuvrent, afin améliorer l’accès à des services en anglais pour cette communauté d’expression anglaise. L’Association collabore étroitement avec une diversité d’organisations et d’institutions du milieu pour contrer les défis rencontrés par la population anglophone en situation minoritaire concernant l’accès aux services sociaux et de santé en anglais. L’avis de l’Association des Townshippers est d’ailleurs souvent sollicité par les instances gouvernementales fédérales, provinciales et municipales, ainsi que d’autres institutions qui font affaire avec la population d’expression anglaise dans la région. Cette approche de réseautage communautaire permet aux professionnel·les de mieux connaître les aîné·es anglophones et d’identifier leurs besoins sociaux et médicaux et de faciliter l’accès aux services sociaux et de santé des usager·ères qui rencontrent des difficultés à trouver l’information sur ces services.